Presenting a native (Islamic-Iranian) model of compassionate parenting based on the opinion of experts - Afkhami Ardekani, Malihe; Vaziri Yazdi, Saeed; Rezapour Mirsaleh, Yasser; Falah, Mohammad Hosein (Applied Family Therapy Journal (AFTJ), 2022)
Aim: One of the important issues in the field of compassionate parenting is the use of styles in accordance with the cultural and indigenous principles of Iranian society. Therefore, the aim of this research was to provide a native (Islamic-Iranian) model of compassionate parenting based on the opinion of experts. Method: This research is of mixed type with the aim of validating the local model. The statistical population of this research in the qualitative and quantitative part will be all specialists in the field of parenting studies and native-Islamic patterns. In the qualitative part, the samples will be selected from among the experts in a targeted way and based on the theoretical saturation of the research experts, and in the quantitative part, in a non-random way. Results: Finally, the conclusion has been reached that the native Iranian Islamic parenting model is compassionate with God-centered components of parents’ behavior, mother’s conditions during pregnancy and breastfeeding, calling children to moral virtues, deep compassion for children, good prayers for parents and children, belief in Valuableness of children, proper education of children, correct and different upbringing in the first, second and third seven years, being a role model for parents’ behavior, reaching the true self, and being a practical person have good quantitative validity and content validity. That is, it can be observed that all the factor loadings of the questions are higher than 0.5, and this indicates the confirmation of the construct validity of the items. Conclusion: during the confirmatory factor analysis, it was also determined that the structural equation model in the present study has a good fit. Therefore, this model has sufficient validity.